H7N9 is a virus worth worrying about - Horby, P.; Tatem, A.J.; Huang, Z.; Gilbert, M.; Robinson, Timothy P.; Wint, G.R.W.; Hayden, F.G.; Van Vinh Chau, N.; Shindo, N.; Carson, G.; Gao, Z.; Hongjie, Y.; et al. (Springer, 2013)
Once again an animal influenza A virus has crossed the species barrier to cause an appreciable number of human cases. Now, two months after the first known human infections with the H7N9 virus, the question is: which of the paths set by previous emerging influenza viruses will it follow? One predecessor, H5N1, generated alarm owing to its high pathogenicity in humans. It has proved to be a tenacious adversary, remaining endemic in poultry across large parts of Asia, but thankfully it has not adapted to humans and person-to-person transmission remains rare. A second, H7N7, caused a number of mostly mild human infections in the Netherlands in 2003, with some evidence of limited person-to-person spread, but extensive poultry culling controlled it. A third, the H1N1 swine influenza virus that emerged in 2009, successfully adapted to humans and caused a pandemic. So will H7N9 prove to be controllable? Will it remain entrenched in animals? Or will it, like the H1N1 virus, stably adapt to humans and cause a pandemic? The fine line between foresight and alarmism can only be drawn in retrospect. Nevertheless, my colleagues and I consider that H7N9 has many of the traits that make a new flu virus worrisome.